DETERMINANTS OF CAPITAL STRUCTURE IN CONSUMER GOODS SECTOR COMPANIES - Rahma, Ira Patiha; Fauzi, Achmad; Indriani, Susi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to examine the impact of company size, profitability, and sales stability on the capital structure of consumer goods sector companies listed on the Indonesia Stock Exchange during the period 2021-2023. This study uses a quantitative approach by utilizing secondary data obtained from financial statements accessible through the idx.co.id website and the respective company websites from 2021-2023. The population of this study consists of 71 companies, with a final sample of 44 companies over three years selected using purposive sampling techniques referring to the Isaac & Michael table. The data were analyzed using multiple linear regression methods, prerequisite tests, classical assumption tests, and hypothesis testing with the help of SPSS 22 software. The research results show that company size and sales stability have a significant positive effect on capital structure, while profitability has a significant negative effect on capital structure. Simultaneously, these three independent variables have been proven to have a significant impact on capital structure.